PENGAWASAN DINAS KOPERASI UKM, PERDAGANGAN DAN PERINDUSTRIAN KABUPATEN KUANTAN SINGINGI TERHADAP DISTRIBUSI GAS ELPIJI 3 KG DI KECAMATAN KUANTAN TENGAH TAHUN 2019 - Satrio, Gilang; ", Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The government determines LPG gas as fuel to meet household needs for the future and the community must switch from kerosene to LPG gas. The use of LPG gas is intended to continuously reduce the use of kerosene fuel. In carrying out this policy, the government must regulate the distribution of LPG gas so that it is right on target use. The Office of UKM Cooperatives, Trade and Industry of Kuantan Singingi Regency in supervising the distribution of 3 Kg LPG refers to the Minister of Energy and Mineral Resources Regulation Number 26 of 2009 concerning the Supply and Distribution of Liquid Petroleum Gas (LPG).This study aims to describe the supervision of the Koperasi UKM, Industry and Trade Office of Kuantan Singingi Regency in the Distribution of 3 Kg LPG Gas in Central Kuantan District in 2019 and to explain the inhibiting factors of this supervision. This research uses descriptive qualitative methods and data collection techniques by observation, literature study and interviews.The result of this research is that the Department of UKM Cooperatives, Industry and Trade of Kuantan Singingi Regency sets performance planning standards in the form of a work program of supervision of retail prices, quantities, targets, quality of 3 Kg LPG. Supervision of cylinder circulation, storage, misuse of 3 Kg LPG gas. Supervising the distribution of hoses, regulators and accessories with SNI standards and conducting socialization. In the implementation of this supervision, several violations were found, such as the absence of a price board by the base, high retail prices, the distribution of 3 Kg LPG that was not right on target and the existence of a base that did not have a business license. Correction of deviations from the violation of the distribution of 3 Kg LPG gas by giving a warning or light sanction in the form of directions and appeals to violators of the 3 Kg LPG gas distribution rule.Keywords: Supervision, Distribution, Trade, Industry, 3 Kg LPG Gas